2022
DOI: 10.3390/ijerph19169980
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Mobile Health Continuance Intention of Elders with Chronic Diseases: An Integrated Framework of ECM-ISC and UTAUT

Abstract: With the deepening of population aging in China, chronic diseases are a major public health concern that threatens the life and health of nationals. Mobile health or mHealth can effectively monitor chronic diseases, which holds vital significance to the alleviation of social pressure caused by aging. To patients with chronic diseases, mHealth cannot give full play to its value, only when it is used in the long term. However, there is not yet research exploring mHealth continuance intention from the perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 64 publications
1
12
1
Order By: Relevance
“…To our surprise, the result of the study has shown that both the main constructs of the UTAUT, performance expectancy and effort expectancy were both not significant predictors of the intention to use mobile health services. The non-significant impact of performance and effort expectancy on the behavioral intention to use does not support previous studies which have indicated the positive effect of these two factors (PE and EE) on the adoption of mobile health services ( 38 , 39 , 41 , 66 , 90 , 91 ). Other studies, however, have corroborated our findings of the non-significant impact of performance expectancy and effort expectancy on the intention to adopt ( 51 , 92 ).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…To our surprise, the result of the study has shown that both the main constructs of the UTAUT, performance expectancy and effort expectancy were both not significant predictors of the intention to use mobile health services. The non-significant impact of performance and effort expectancy on the behavioral intention to use does not support previous studies which have indicated the positive effect of these two factors (PE and EE) on the adoption of mobile health services ( 38 , 39 , 41 , 66 , 90 , 91 ). Other studies, however, have corroborated our findings of the non-significant impact of performance expectancy and effort expectancy on the intention to adopt ( 51 , 92 ).…”
Section: Discussioncontrasting
confidence: 98%
“…This integration is expected to contribute to the mobile health literature by demonstrating the moderating impact of mobile self-efficacy on the relationship between both the performance and effort expectancy of mobile health services and the behavioral intention to adopt mobile health services. While studies have shown the direct impact of performance expectancy and effort expectancy on the behavioral intention to use mobile health services (37)(38)(39)(40)(41)(42), no studies to the best of our knowledge have explored the moderating impact of mobile self-efficacy on these two relationships. This is the first attempted set of contributions to this study.…”
Section: Introductionmentioning
confidence: 99%
“…This study is novel as it combined constructs from social support, UTAUT, and PMT to examine expectant mothers' continued utilization of digital health information. It is also significantly distinct from previous works in continuance intention (Alsyouf, Ishak and Abdullah, 2018;Imlawi and Gregg, 2020;Yang and Jong, 2021;Tian and Wu, 2022).…”
Section: The Structural Modelmentioning
confidence: 58%
“…The model was assessed using 18 measurement items, excluding all demographic variables. The ESPSM items were adapted from the work of Lin, Wang and Hajli (2019), the SMHIU items were from Venkatesh et al (2003) and Puspitasari and Firdauzy (2019). Additionally, the SMHIC items were developed based on items from Chiu, Cho and Chi (2020), while the PS and PV were adapted from Jun, Park and Cho (2019) and Shatta et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The UTAUT model has a wide range of applications in the field of smart aging [ 12 , 23 , 24 , 25 , 26 , 27 ]. Since smart aged-care products are a relatively new type of product, an integrated technology acceptance model can help us explore the key factors affecting the adoption of smart aged-care products by the aged.…”
Section: Literature Researchmentioning
confidence: 99%